Tanggung Jawab Pengusaha Terhadap Keselamatan Tenaga Kerja Pemasangan Wi-Fi Rumah : (Studi Kota Mataram) - Mukhlas Muliamar; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the employer's responsibility for the safety of the home wi-fi installation workforce and the factors that affect the safety of the home wi-fi installation workforce. The type of research used is normative-empirical law with the approach method used by legislation (statute approach), conceptual approach (conceptual approach) and Sociological Approach (Social Approach). The results showed The responsibility of the entrepreneur PT. Netzen Media Access, PT. Icomnets Plus, and PT. Media Facilities Data on labor safety, namely, First Aid and BPJS Employment. Factors that affect workers can be internal factors, caused by human error and external factors caused by the work environment and weather.